Antiknock Performance of Interlayered High-Damping-Rubber Blast Door under Thermobaric Shock Wave. (2nd June 2016) - Li, Xiudi; Miao, Chaoyang; Wang, Qifan; Geng, Zhengang
Abstract : The long duration and high impulse shock wave of thermobaric bomb threatens the security of underground structures. To obtain high resistance blast door against thermobaric shock wave, firstly, the dynamic mechanic property of high damping rubber was studied by split Hopkinson pressure bar (SHPB) equipment and the stress-strain relationship of high damping rubber under average strain rate of 5200/s was obtained. Secondly, the numerical model of interlayered high-damping-rubber blast door was established with ANSYS/LS-DYNA code based on test results, and the antiknock performance of interlayered high-damping-rubber blast door under thermobaric shock wave was analyzed by contrast with ordinary blast door. The results showed that the midspan displacement of the blast door decreased firstly and then increased with the increase of thickness of the high-damping-rubber interlayer, and the optimal thickness of the high-damping-rubber interlayer for energy consuming was 150 mm in the calculation condition of this paper. With the increase of the distance between the interlayer and the front surface of the door, the midspan displacement of the blast door decreased continually. The midspan maximum displacement of interlayered high-damping-rubber blast door decreased 74.5% in comparison to ordinary blast door. It showed that the high-damping-rubber structure can effectively improve the antiknock performance of blast door under thermobaric shock wave.